Unified Theoretical Foundations of Lift and Drag in Viscous and Compressible External Flows - Liu, Luo-Qin (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis analyzes aerodynamic forces in viscous and compressible external flows. It is unique, as the force theories discussed apply to fully viscous and compressible Navier-Stokes external flows, allowing them to be readily combined with computational fluid dynamics to form a profound basis of modern aerodynamics. This thesis makes three fundamental contributions to theoretical aerodynamics, presenting: (1) a universal far-field zonal structure that determines how disturbance flow quantities decay dynamically to the state of rest at infinity; (2) a universal and exact total-force formula for steady flow and its far-field asymptotics; and (3) a general near-field theory for the detailed diagnosis of all physical constituents of aerodynamic force and moment.